Greta Dole: capstone - Greta, Dole, artist (Colorado State University. Libraries, 2026)
The artist's statement: I created this poster for my Advanced Illustration to be submitted for a Mexico poster contest. I was inspired to create a poster on the theme of sports and peace. I grew up as a female athlete and have been inspired by the accomplishments that female athletes have made. I made the poster colorful and eye-catching because the achievements of female athletes have been eye-catching and incredible to witness. These athletes have worked hard in their sport to be noticed and show the importance of female sports, so I created that feeling in a poster, athletes in action.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design